In vitro antiplasmodial activity of 1,10- phenanthroline derivatives and its quantitative structure-activity relationship - Mustofa, Mustofa (Universitas Gadjah Mada, 2003)
Background: Previous study showed that 1,10-phenanthroline skeleton were active in vitro on both Plasmodium falciparum chloroquine-resistant and -sensitive strains. Based on the skeleton, a series of 1,10-phenanthroline derivatives have been synthesized. However the antiplasmodial activity of those molecules has not been reported.Objective: To know the in vitro antiplasmodial activity of thirteen 1,10-phenantroline derivatives and its quantitative structure-activity relationship.Methods: The in vitro antiplasmodial activity was tested on two strains of Plasmodium falciparum, FcB1Columbia (chloroquine-resistant strain) and a Nigerian (chloroquine-sensitive strain) using a radioactive micromethod. The parasite growth was estimated by [3H1-hipoxanthine incorporation after 24 and 48 hours incubation with each molecule tested. The control parasite free from any molecules was referred to as 100% growth. For this radioactive method IC5o value showing concentration inhibiting 50% of the parasite was determined graphically in concentration versus percent inhibition curves. The quantitative structure-activity relationships (QSAR) of 1,10-phenanthroline derivatives were investigated using atomic net charges as predictors of their activity. Data of predictors were obtained using semi-empirical Austin Model 1 (AM1) calculation method. The possible linear relationships of in vitro antiplasmodial activity with atomic net charge parameters of those compounds were studied. The best model QSAR was evaluated by multiple linear regression method.Results: The results showed that the IC5o values of 1,10-phenanthroline derivatives range from 0.02 to 11.05 uM for the FcB1 strain and from 0.14 to 19.84 pM for the Nigerian strain. The molecure (4), 2,10- methy1-3-12-chloroethyl)-4-chloropirydo [2,3-i] quinolineium iodide exhibited the best in vitro antiplasmodial activity with an IC50 value ranging 0.02 to 0.16 1.1M. The best model QSAR was expressed by log IC5o = -3.4398 - 14.9050 qN1 - 8.5589 qC10 - 14.7565 qC7 + 5.0457 qC11 (n = 13; r = 0.96275; r2 = 0.92689; SE = 0.61578 and F (4,8) = 25.3556).Conclusion: The molecule (4) yield the best in vitro antiplasmodial activity on both P. falciparum strains. In addition, there is correlation between antiplasmodial activity and atomic net charges of atoms on the 1,10-phenanthroline skeleton.Key words : 1,10-phenanthroline, antiplasmodial activity, quantitative structure-activity relationships